Human rights according to Islamic reformist jurists in Iran - Najafinejad, Alireza (2012)
This research has studied the subject of Human Rights in the Thoughts of Islamic Reformist Jurists in Iran after the Islamic Revolution. The objectives of the research is to present an in-depth understanding of the framework of reformist jurists approach to human rights, to elicit principle of human rights in the thought of reformist Jurists in Iran, and to formulate interpretation of Shari’a in thoughts of Islamic reformist jurists with respect to human rights. The primary data are selected among speeches, interviews, verdicts and the books that are written by the main reformist thinkers. Qualitative content analysis is the method of the research for analyzing of information. The Islamic reformist jurists try to present new ideas and interpretation by using ijtihad in principle and reduce the conflicts between jurisprudence and human rights as much as it is possible. The finding demonstrated that it seems even these new ideas are still far from human rights. The Islamic reformist jurists try to demonstrate that, there isn't any discrimination between the human, but they do not accept the freedoms of opinion, changing the religion, speech and the religious and sexual equality and democracy through which they indicate the purpose of human rights. Moreover, the finding also shows that, those ideas which were stated under the title of dynamic Jurisprudence are still not the viewpoint of the majority of jurists and in fact, these decrees are not the ideas of all jurists. The study also demonstrated that according to the gained result from this investigation, they merely pay attention to human rights on account of the problems caused in the Islamic societies.